Targeting TSPEAR-AS2 suppresses tumor growth and interferon signaling in esophageal cancer - Chunyan Zhang; Yuanbo Cui (Scientific Reports)
Abstract Dysregulation of long non-coding RNAs (lncRNAs) and interferon signaling contributes to tumorigenesis and progression; however, their crosstalk in tumor biology remains poorly understood. Here, we showed that TSPEAR-AS2, an lncRNA mediated by METTL1, activates the interferon signaling pathway in esophageal cancer (ESCA). Clinically, we conducted a pan-cancer investigation and identified TSPEAR-AS2 as a novel ESCA-related lncRNA that predicts a worse patient prognosis. The high expression of TSPEAR-AS2 was validated in multiple ESCA cohorts, demonstrating that this lncRNA had good diagnostic performance. METTL1, an RNA N7-methylguanosine (m7G) methyltransferase, was positively correlated with TSPEAR-AS2 expression in ESCA tissues, and METTL1 was found to induce TSPEAR-AS2 expression in ESCA cells. Functionally, the up-regulation of TSPEAR-AS2 promoted proliferation, cell cycle progression, migration, and stemness in ESCA cells, whereas its knockdown attenuated these malignant phenotypes. Furthermore, both TSPEAR-AS2 deficiency and antisense oligonucleotide (ASO)-based intratumoral intervention could significantly suppress tumor growth in vivo. Mechanistically, quantitative proteomic analysis revealed that TSPEAR-AS2 ablation altered the expression of functional proteins related to interferon signaling pathways, such as HLA-E, IRF3, and IFITs. These findings identify a previously unrecognized role of the METTL1/TSPEAR-AS2/interferon signaling axis in ESCA development and suggest that TSPEAR-AS2 is a potential prognostic indicator and therapeutic vulnerability for this malignancy.